Self-Control, Injunctive Norms, and Descriptive Norms Predict Engagement in Plagiarism in a Theory of Planned Behavior Model - Curtis, G.; Cowcher, E.; Greene, B.; Rundle, K.; Paull, M.; Davis, Melissa (Springer Netherlands, 2018)
The Theory of Planned Behavior (TPB) predicts that a combination of attitudes, perceived norms, and perceived behavioral control predict intentions, and that intentions ultimately predict behavior. Previous studies have found that the TPB can predict students’ engagement in plagiarism. Furthermore, the General Theory of Crime suggests that self-control is particularly important in predicting engagement in unethical behavior such as plagiarism. In Study 1 (N = 229), we incorporated self-control in a TPB model and tested whether norms, attitudes, and self-control predicted intention to plagiarize and plagiarism behavior. The best statistical fit for the path-analytic model was achieved when a direct path from self-control to plagiarism engagement was specified. In Study 2 (N = 320), we added a measure of perceived behavioral control and split the measurement of norms into descriptive (normal behavior) and injunctive (good behavior) components. This study found that both self-control and perceived-behavioral control additively contributed to the prediction of plagiarism and the path-analytic model achieved its best fit when direct paths from perceived norms to plagiarism behavior were specified. These studies suggest that setting strong anti-plagiarism norms, such as by the use of honor codes, and seeking to enhance students’ self-control may reduce engagement in plagiarism.